Guidelines for the Management of Primary Systemic Vasculitis - Rizzo, Toni (MD Conference Express, 2012)
Antineutrophil cytoplasmic antibody-associated vasculitis (AAV) comprises a group of rare, potentially life-threatening conditions that can be fatal if untreated. These diseases include granulomatosis with polyangiitis, (previously known as Wegener granulomatosis), Churg-Strauss syndrome, and microscopic polyangiitis. These complex conditions are characterized by systemic illness and multisystem disease, with vasculitis that can lead to aneurysm formation, hemorrhage, and infarction [Watts RA, Scott DG. Curr Opin Rheumatol 2003]. This article discusses the management of AAV.